2011
DOI: 10.1590/s1679-62252011005000007
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in fish composition and abundance in a perennial tributary of the rio Paraguaçu, a little-known drainage in the Brazilian semi-arid region

Abstract: The rio Santo Antônio is a perennial lowland stream in the Brazilian semi-arid region, and is the main tributary of the upper rio Paraguaçu, an important drainage of the Chapada Diamantina. The temporal variation of the fish composition and abundance in a stretch of the middle course of the river was evaluated. Sampling was carried out monthly between August 1998 and July 1999, using standardized gear and techniques. Data on water and air temperature, water transparency, maximum and mean depth, width and area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
4
0
5
Order By: Relevance
“…Studies as (Lowe-McConnell, 1999;Fernandes et al, 2009) observed contrasting communities between seasons in tropical headwater streams. However, Mazzoni et al (2006) and Santos & Caramaschi (2011) found that the abundance of a few small species are related to temporal variations in the hydrologic regime. Therefore, it is difficult to observe a general pattern of fish communities composition (Novakowski et al, 2008).…”
Section: Assemblage Structure and Compositionmentioning
confidence: 99%
“…Studies as (Lowe-McConnell, 1999;Fernandes et al, 2009) observed contrasting communities between seasons in tropical headwater streams. However, Mazzoni et al (2006) and Santos & Caramaschi (2011) found that the abundance of a few small species are related to temporal variations in the hydrologic regime. Therefore, it is difficult to observe a general pattern of fish communities composition (Novakowski et al, 2008).…”
Section: Assemblage Structure and Compositionmentioning
confidence: 99%
“…Neste estudo, setembro/2010 apresentou as médias mais baixas de temperatura, bem como a menor riqueza e abundância de espécies. Santos & Caramaschi (2011) também verificaram diferenças na temperatura entre a época seca e chuvosa, sendo esta variável uma das que mais correlacionaram com abundância dos peixes. Em rios tropicais a comunidade de peixes é afetada pelas mudanças sazonais, já que esta expande o ecosistema aquático da época seca para a chuvosa (Santos & Caramaschi, 2011).…”
Section: Discussionunclassified
“…Santos & Caramaschi (2011) também verificaram diferenças na temperatura entre a época seca e chuvosa, sendo esta variável uma das que mais correlacionaram com abundância dos peixes. Em rios tropicais a comunidade de peixes é afetada pelas mudanças sazonais, já que esta expande o ecosistema aquático da época seca para a chuvosa (Santos & Caramaschi, 2011). Variações na abundância em decorrência da sazona lidade podem refletir mudanças na estrutura da assembleia de peixes.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…From the 19th century until the 1980s, the rivers of the Chapada Diamantina were impacted by mechanized diamond mining and this exploration resulted in drastic changes in the riverbeds and banks due to burning the vegetation and soil excavation. At present, the main impacts are related to the deforestation and unregulated tourism activities (Santos & Caramaschi, ). Notwithstanding the importance and the high incidence of different types of environmental degradation, no studies on the environmental quality of the rivers have been carried out.…”
Section: Introductionmentioning
confidence: 99%